The Effect of Using Authentic Materials on the Performance of Jordanian EFL Learners’ Reading Comprehension - Alshra’ah, Mohammad Awwad (Journal of Curriculum and Teaching Methodology, 2022)
This study aimed at investigating the effect of using authentic reading materials on the performance of Jordanian EFL learners’ reading comprehension. The participants of the study were 53 9th grade Jordanian EFL students during the second semester of the academic year 2020/2021 from the Northeastern Badia Directorate of Education who were assigned randomly into two groups: an experimental group, which consisted of 26 students, and the control group, which consisted of 27 students. The control group was taught conventionally by using the instructions of the Teachers’ Book while the experimental group was taught by using authentic materials. Both groups sat to a pre-test to assure that both groups have the same actual level in reading comprehension skills (scanning, skimming, summarizing, brainstorming and making decision) before executing the experiment. Data were collected within eight weeks. Students of both groups sat to a post-test to see if any change occurred, if it occurred, to what extent, and in what dimension. Descriptive statistics, T-test and One-way ANOVA were used to analyze data. The findings showed that using authentic reading materials significantly improved all reading comprehension skills in general and in scanning and skimming in particular.